2011
DOI: 10.1016/j.ejca.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Determining circulating endothelial cells using CellSearch system during preoperative systemic chemotherapy in breast cancer patients

Abstract: Baseline CEC, in particular CD34(+)CEC, counts and the CD34 positive rate might be useful for the prediction of treatment response of preoperative chemotherapy in patients with operable breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…These findings are in accordance with those by Wierzbowska et al, who observed that the levels of CECs and EPCs were significantly higher in AML patients than in the control group by a 17-and 18-fold, respectively (13). This is in concordance with previous studies in multiple myeloma (MM), metastatic carcinoma, myelodysplastic syndrome, gastrointestinal stromal disease (GIST), hepatocellular carcinoma, breast cancer, non-Hodgkin's lymphoma (NHL), myelofibrosis and chronic lymphocytic leukemia (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are in accordance with those by Wierzbowska et al, who observed that the levels of CECs and EPCs were significantly higher in AML patients than in the control group by a 17-and 18-fold, respectively (13). This is in concordance with previous studies in multiple myeloma (MM), metastatic carcinoma, myelodysplastic syndrome, gastrointestinal stromal disease (GIST), hepatocellular carcinoma, breast cancer, non-Hodgkin's lymphoma (NHL), myelofibrosis and chronic lymphocytic leukemia (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionsupporting
confidence: 82%
“…by the use of different chemotherapy agents (11). Additionally, CECs and EPCs could be used as a novel marker for minimal residual disease in chronic myeloid leukemia, as reported by Wu et al (12).…”
Section: Circulating Endothelial Cells and Their Progenitors In Acutementioning
confidence: 75%
See 1 more Smart Citation
“…Some studies are not suitable for deriving the predictive value due to their small sample size [13,14,15,16]. We focused on recent data showing that CTCs may represent novel tumor biomarkers for predicting the response to NCT in LABC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it may be used in the field of diagnostic follow-up, determining the response to treatment and prognosis of the disease (Ali et al, 2011).…”
Section: Introductionmentioning
confidence: 99%